A novel model used for assessing supply chain sustainability integrating the ANP and ER approaches and its application in marine ranching - Wan, Xiaole; Liu, Xiangtong; Du, Zhuoqian; Du, Yuanwei (Journal of cleaner production, 2021)
The evolution of competition has set greater demands for supply chain sustainability. As the existing models mostly consider the issue only by employing the triple bottom line (TBL), this paper aims to establish a novel supply chain sustainability assessment model. Firstly, this paper establishes the indicator system from dimensions of TBL and supply chain capability, and integrates innovation and value co-creation. Innovation can help enterprises improve sustainability and benefit from it. Value co-creation has also become a new source of sustainable competitive edge. Compared with the previous qualitative research, the combination of quantitative and qualitative indicators used in this paper can more objectively reflect the subject. Secondly, this paper employs the Analytic Network Process (ANP) method to determine the weight of indicator. This method breaks the hypothesis of independence and considers the interactions among indicators. Thirdly, the Evidential Reasoning (ER) method is used to process expert evaluation information of qualitative indicators by membership function. This method incorporates the idea of fuzziness, allows experts to make no evaluation on unfamiliar indicators. Finally, this paper validates the practicability through a case study of marine ranching. The contribution lies in that this paper provides a novel theoretical model for supply chain sustainability assessment. •We establish a novel supply chain sustainability assessment indicator system based on TBL and supply chain capability, including innovation and value co-creation dimensions.•Adopting the ANP and ER methods, we build a new SSCM assessment model including innovation and value co-creation dimensions.•Marine ranching is adopted as a case study to demonstrate the feasibility of the novel model.